Systematic literature review: mapping the topology of a decade of the talent management research - Ghafar, Nor Hisham; Mohd Salleh, Lailawati (2015)
Talent management (TM) is one of the areas in the human resource management that has continuously attracted the interest of scholars. This paper reviews past TM literature and maps the topology of talent management research in the past 10 years (2004 to 2014). By employing a systematic literature review technique, based on the Australian Business Deans’ Council (ABDC) ranking, 72 articles from 20 high quality journals were identified as the main data source to generate information on the past focus of TM topics, the method and data collection techniques employed, and the underpinning theories used in the TM literature within the last decade. The result from this review highlights potential gaps possible for future research.